Lecture assessment system (manage student attendance module and manage marks module) - Saringat, Mohd Zainuri (2003)
Kolej Universiti Teknologi Tun Hussein Onn (KUiTTHO) had been awarded the Quality Management System Standards ISO 9001: 2000. Unfortunately, there are still some problems on its student's assessment. At the end of a semester, mostly happen certain students had no marks but they had registered on the Student Information System. When comes to the end of the semester, there is too late to solve this problems. Its happens because of the students register the subject but they did not attend the class and sometime they attended on other class which is the same subject. In certain case, the lecturer miss transfer the students mark to the computer form. The management had introduced a general format to the lecturer to keep the students assessment record. After implement this format, the same problem still happened but the number of cases is reducing. The Lecture Assessment System becomes an alternative way to overcome this problem. Through this system, the management can monitor the students' progress marks with their attendance. Furthermore, the Lecture Assessment System is a web-based application.